Behaviour of ultra high performance fibre- reinforced cementitious composite for enhancing the fire endurance of structural members / Sobia Anwar Qazi - Anwar Qazi, Sobia (Institute of Graduate Studies, UiTM, 2016)
Fibre-reinforced polymer (FRP) strengthened and unstrengthened reinforced concrete (RC) structures are susceptible to intense deterioration when exposed to elevated temperatures, particularly in the incident of fire. FRP has the tendency to lose bond with the substrate due to the low glass transition temperature (Tg) of epoxy; the key component of FRP matrix. Previously, various types of high performance cementitious composites (HPCC) were explored for the protection of RC structural members against elevated temperature. However, there is an inadequate information on the influence of elevated temperature on the ultra high performance fibre- reinforced cementitious composites (UHPFRCC) containing ground granulated blast furnace slag (GGBS) and/or fly ash (FA) as a replacement of high alumina cement (HAC) in conjunction with hybrid fibres (basalt and polypropylene (PP) fibres). This could be a prospective fire resisting material for the structural components. The influence of elevated temperatures on the compressive, flexural and tensile strength of UHPFRCC, made of HAC-GGBS and hybrid fibres, was examined in this study along with complete microstructural, chemical and thermal analysis. Total fourteen (14) mixes were developed. Besides control sample (without fibres), three other samples, containing 0.5%, 1% and 1.5% of basalt fibres by total weight of mix and 1 kg/m3 of PP fibres, were prepared and tested. Another mix was also prepared with only 1 kg/m3 of PP fibres. Nine (9) more mixes were developed with the replacement of GGBS with FA…